RETROFITTING REINFORCED CONCRETE BEAMS USING CARBON FIBER REINFORCED POLYMER SHEETS AFTER EXPERIENCING FLEXURAL CRACKING DAMAGE - Purba, Luki Hariando; Lumbangaol, Partahi; Saragi, Yetty Riris (Jurnal Infrastruktur, 2026)
This study investigates the retrofitting of reinforced concrete beams that have experienced flexural damage due to overloading using Carbon Fiber Reinforced Polymer (CFRP) sheets. The tested beam had previously developed flexural cracks and tensile steel yielding but had not reached complete collapse, indicating the presence of residual structural capacity and ductility. Prior to strengthening, the existing cracks were repaired using Sikadur-31 CF epoxy to restore continuity in the damaged region. Subsequently, CFRP sheets were externally bonded along the tension face to enhance flexural performance. Experimental testing was conducted using a two-point loading system to evaluate load–deflection behavior, crack propagation, stiffness, and failure mode before and after repair and strengthening. The results showed that the retrofitted beam achieved a significant improvement in structural performance. The maximum load capacity increased by approximately 20.47%, accompanied by enhanced stiffness, while the ultimate deflection remained nearly unchanged. This indicates that the beam became stronger without a significant loss of deformation capacity within the tested range. Crack patterns after strengthening remained dominated by the tension zone, confirming a flexural behavior. Failure was initiated at the CFRP segment joints rather than in the compression zone, highlighting the importance of bond and joint detailing in CFRP applications. Overall, the study demonstrates that beams with prior flexural damage and steel yielding can be effectively rehabilitated and strengthened using CFRP, provided that sufficient residual ductility remains and proper design considerations are applied to avoid brittle failure.